Odpowiedzialność karna za przestępstwa przeciwko bezpieczeństwu w ruchu oraz eksploatacji pojazdów według KK Ukrainy - Burdìn, Volodimir (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2015)
This article is concerned with problems of criminal responsibility for criminal offences against traffic safety and safety of transport operation. Today it is devoted a separated Section XI of Special Part «Criminal offenses against traffic safety and safety of transport operation» in the current Criminal Code of Ukraine. The title of this section indicates that there are combined offenses related to violation of safety rules in the field of transport usage. The article points out that the security rules do not exist for the sake of rules and therefore its cannot be the object of criminal law protection and do not create district types of social relations of traffic safety or safety of transport operation in the capacity of such object. Whatever regardless of the fields all safety rules focuses on the protection of real social relations including life, health, property, environment etc. The main purpose of the safety regulations first of all is to create a safe conditions for human life and health and to a lesser extent these rules also protects property relations. At the same time, social relations that ensure the normal operation of transport must be considered as the main direct object of these crimes. Other objects of criminal law protection within the relevant offenses can only serve as additional objects. Only in this case framing logic of the Criminal Code of Ukraine construction will not be disturbed.Instead, the certain offenses analysis of Section XI indicates that the legislator actually provides criminal legal protection only for one object – to human life or health. Therefore, a special rule which provides liability for causing injury to life or human health as a result of violation of the relevant rules of traffic safety or safety of transport operation is creating. Such regulatory structures determine questions about advisability of selection of such special rules in Special part of the Criminal Code of Ukraine. Actually they can be replaced by qualifying signs that will point to specific violations of safety rules in general rules of crimes against life and human health or property. However, this kind of separate specific rules allows us to assert the existence of the large number of so-called covert crimes against life and human health in Section XI of the Special part of the Criminal Code of Ukraine.Particular attention is paid to the problems concerning to the criminal responsibility for offense under Article 286 of the Criminal Code «Violation of rules related to traffic safety and safety of transport operation by persons who drive a vehicle». The conclusion that in practice enforcement officers don’t pay enough attention to determine guilt of the person who violated the rules has been substantiated. As author thinks that it leads to weaken the criminal responsibility of drivers who intentionally violate these rules in some cases.It is proved that general offenses against life and human health that involve infliction of bodily injury or death must be completed by new qualifying sign which provides such consequences in connection with a source of increased danger. This qualifying sign along with the qualifying sing that would point out a violation of special safety rules will allow refusing a significant number of special rules including the rules provided in Section XI of the Special Part of the Criminal Code.
Keywords: przestępstwo; bezpieczeństwo ruchu; pojazdy; odpowiedzialność karna; zróżnicowanie odpowiedzialności karnej